The European Union's Mediterranean Policy in the Context of the "Arab Spring" - V. A. Latkina (Vestnik MGIMO-Universiteta)
The article discusses the policy of the European Union aimed at the export of its democratic values, acquis communautaire and governance models to the neighbour countries in the Southern Mediterranean. The process of Europeanization reflects a particular case of global megatrend -democratization which in its turn positioned as democracy promotion through soft power instruments. From the EU point of view the goal of the Barcelona process launched in 1995 was to construct Euro-Mediterranean Partnership and common identity in order to promote democratic transitions in Southern Mediterranean. While the EU Foreign Policy in the Mediterranean region was historically conditioned by the security interests of the European Union, it suffered from securitization/democratization dilemma. The article analyses the process of external Europeanization in the Southern Mediterranean as a regional dimension of global democratization process in the context of Union for the Mediterranean development before and after the Arab Spring and new approach in the framework of the ENP Partnership for Democracy and Shared Prosperity with the Southern Mediterranean. The article proposes that the lack of political strategic vision in the EU toward the Arab democratic transition during 2011-2013 narrows its role as a transformative democratic power, hinders Europeanization/ democratization process in the macro-region of North Africa and Middle East and presents the EU with a new dilemma - to continue its traditional democratization policy or to shift towards a more pragmatic approach to cooperating with new Arab regimes.